Carnivore coexistence without competition: giant otters are more nocturnal around dens than sympatric neotropical otters - Norris, Darren; Michalski, Fernanda (PeerJ, 2024)
Nocturnal activity of tropical otters is rarely reported. To date no studies have documented den use by sympatric giant (Pteronura brasiliensis) and neotropical otters (Lontra longicaudis). We used camera-traps to monitor den use by sympatric otters along an equatorial Amazonian river. Camera-traps provided evidence that giant otters were more nocturnal around dens than sympatric neotropical otters. Nocturnal activity was recorded in 11% of giant otter photos (n = 14 of 125 photos), but was recorded only once for neotropical otters. Den use by giant and neotropical otters overlapped spatially and temporally but not concurrently. We hypothesize that previously reported nocturnal activity in neotropical otters is facilitated by the absence or low density of giant otters. Our results also underscore the need to use complementary techniques together with den counts for monitoring otters as sympatric species can use the same dens.
Keywords: Activity; Amazon; Camera trap; Carnivore; Coexistence; Den; Mammal; Mustelid; Otter; Vertebrate